Orthoses for dynamic stretching of contractures of knee joints in children - Bayev, Pavel; Pivovarov, Viktor; Korneev, Sergey; Petrov, Vladymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Conservative treatment of knee joint contractures with dynamic orthoses (DO) is an important step in rehabilitation of children with pathologies of the musculoskeletal system. Objective: To determine the possibility of using DO on knee-ankle joint (foot) with pneumatic cylinders and knee joints with a flat spiral spring for conservative treatment of contractures of knee joints in children. Methods: 7 children completed a course of rehabilitation treatment with new designs of DO (with knee joints with a flat spiral spring or pneumatic cylinders) for flexion contractures of knee joints with the background of neurological diseases. The feature of DO with a flat spiral spring is the ability to perform dynamic linear correction of flexion/extension contractures of knee joints. The use of hinges allows the use of a constant correction force, which is created using a selected individually adjustable flat spiral spring, over a long period. DO with pneumatic cylinders allow to carry out dynamic correction of the flexion contractures of the knee joint with a linear force that depends on the gas pressure in the pneumatic cylinder and usually decreases by 30 % in case of complete compression of the latter. Results: The testing of the proposed DO confirmed the effectiveness of their use and the expediency of introduction of new designs of orthopedic products at Ukrainian industrial enterprises. Conclusions: Conservative treatment with new designs of DO for stretching of knee joint contractures in children is a sufficiently effective means of eliminating the pathological position of the joint and restoring a significant amount of movement in it. The designed constructions of DO will allow an individual approach to each patient, depending on the nature of the disease, its severity and the anatomical features of the child.